How do learning orientation and strategy yield innovativeness and superior firm performance? - M. Dülger; G. Alpay; C. Yılmaz; M. Bodur (South African Journal of Business Management, 2014)
This paper attempts to shed light on the role of learning orientations of firms and their adoption of Porter's generic strategies on four dependent variables: Behavioral innovativeness, product innovativeness, technological innovativeness and, ultimately, firm performance. Hierarchical regressions were run with data from a random sample of 121 firms operating in Turkey. Findings indicate that internally-focused learning, market-focused learning and differentiation strategy have significant effects on the three innovativeness dimensions. When firm performance is included as the eventual outcome variable into the analysis, internally-focused learning, focus strategy and product innovativeness emerge as its main predictors. In fast-paced, highly unpredictable market environments, managers can make use of these findings to their benefit in terms of elevating their firms' innovativeness and performance levels.
Keywords: 650